The future of apple growing in the Northern Great Plain region - Harsányi, Gergely; Nyéki, József; Soltész, Miklós; Gonda, István; Szabó, Zoltán (Acta Agraria Debreceniensis, 2005)
We revealed and assessed those macroeconomic data which enabled us to identify the outstanding role of agriculture and within it that of fruit production. Based on this, it can be said that soil is the most important natural resource of Hungary. The appropriate combination of the additional resources required for production, labour and assets can provide a comparative advantage for the Northern Great Plain Region.The Northern Great Plain Region is one of the most underdeveloped regions in Hungary, so its development is a political objective. When analysing the economic sectors in the region, the important role of agriculture is obvious and it is also clear that the industry and the tertiary sector can only have an alternative income generating role in the future also. Therefore, it is important that the regional development funds of Hungary and the European Union are directly or indirectly aimed at improving agricultural development and competitiveness.